From 'Please sir, stay out of it' to 'You are an abomination': (in)civility and emotional expression in emails sent to politicians. Issue 5 (4th April 2021) - Rohlinger, Deana; Vaccaro, Christian
ABSTRACT: Despite the excellent research on incivility in social spaces, it is unclear if this pattern of meanness holds true in more personal communication such as email. Drawing on an original sample of 2, 509 e-mails sent to Florida Governor Jeb Bush in response to his efforts to reinsert the hydration and nutrition tubes of Terri Schiavo, we analyze how individuals differentially use (in)civility and emotional expression in their claimsmaking. We find that emails sent to Bush about the Schiavo case are largely polite, even when individuals' disagreed with Bush's intervention on Terri's behalf. At the same time, we find a lot of emotional expression in the emails, and that the first emotional expression typically was negative. In order to better understand the relationship between (in)civility and emotion, we qualitatively analyze the 383 emails containing incivility, and find that individuals directed their negative emotional expressions at different targets. Additionally, we see different patterns in how negative emotional expressions are paired with uncivil communication according to the target. Emailers expressing negative emotions and incivility at Bush largely criticize him for violating individual rights, and, nearly half, blast him for prioritizing the Schiavo case over other problems facing the state. In contrast, emailers using uncivil language and negative emotional expressions at Terri's husband and a prominent judge try to persuade Bush to hold one or both of these men accountable for Terri's death. We conclude the paper by underscoring the utility in analytically distinguishing emotional expression from (in)civility.